sepak bola adalah cabang olahrag Pendidikan olahraga dan kesehatan jasmani: Pendidikan olahraga dan kesehatan - Imat, irwanshapryo (Pusat Pengembangan Olahraga Universitas Pahlawan, 2023)
Football is a team sport that requires good teamwork, therefore each player must master all the parts and basic techniques and skills of playing soccer. Without mastering the basics of techniques and skills to play soccer well, then players will not be able to carry out game patterns or develop modern tactics and will not be able to read the game. The formulation of the problem in this study is how the basic technical skills of soccer games for players aged 12-13 years at the PSD Club of Demak Regency. This study aims to determine the basic technical skills of playing soccer on players aged 12-13 years at the PSD Club, Demak district. The population of this study were participants who took part in soccer training at the PSD of Demak district in 2009 totaling 55 participants. In this study using total sampling so that the sample used is all participants who take part in soccer training at the PSD of Demak Regency, totaling 55 participants. Based on the results of research on participants who took part in soccer training in PSD Demak district through 5 kinds of test items, it was found that the basic technical skills of playing soccer in participants who took part in soccer training in PSD Demak district were classified as moderate, it was proven that 30.91% had basic skills. Playing soccer in the good category, 60.00% in the moderate category and the remaining 9.09% in the moderate category. Based on the results of the research and discussion conducted, it can be concluded that the basic technical skills of soccer games for players aged 12-13 years at the PSD Club of Demak Regency are in the medium category. Based on the results of these studies, the researchers suggest that the provision of basic technical training to play soccer should be given from an early age so that it is more easily understood and mastered by players